Memórias fraturadas: passado, identidade e imaginação em Borges e Mutarelli - Pedro Galas Araújo (Estudos de Literatura Brasileira Contemporânea, 2011)
Memory forms the identity of a collectivity as well as that of the individual: it is the point from which we construct a narrative that organizes our subjectivity. However, it is defective, lacking, accomodating. How can we thus have the identi- ty built upon such unstable ground? Still, the last decades of the twentieth century were marked by what Andreas Huyssen calls of “culture of memory”: an appre- ciation of the past as an element that gives coherence to our own experience, as op- posed to a fractured present, which offers no glimpse of a promising future. This paper discusses such issues through the dialogue between the stories “O outro” and “Funes, o memorioso”, by Jorge Luis Borges, and the comics narrative “A caixa de areia ou eu era dois em meu quintal” by Lourenço Mutarelli, including aspects such as identity construction and the use of imagination in that operation.